Illuminating human‐rare historic book interaction. Issue 1 (24th October 2017) - Sonnenwald, Diane H.; McElligott, Jason
ABSTRACT: This presentation showcases research that is investigating human‐rare historic book interaction in order to develop a theoretical framework that takes into account the materiality of rare books and will form a foundation for technology requirements that will allow individuals to more fully experience rare historic books through the use of virtual or augmented reality technology.